Development of Learning Instruments for Improving Movement and Balance among Students with Visual Impairment at Thammikkawittaya School in Phetchaburi Province - Thangthong, Prachom (Area Based Development Research Journal, 2023)
In order to enhance the quality of life and maximize the potential of students with visual impairment, improvements are necessary. However, current exercise methods are unsafe as they lack specialized instruments designed for this group. Therefore, this research focuses on developing learning instruments to improve movement and balance among visually impaired students at Thammikkawittaya School in Phetchaburi Province of Thailand. The research process involved: 1) collecting data on the sample group and relevant individuals for further analysis, 2) analyzing the exercise patterns, movement, and balance of the sample group, 3) developing a set of integrated learning instruments to improve movement and balance skills for visually impaired students, and 4) summarizing the results. The set of learning instruments includes a full-body harness, an assistive device for stability and movement, and handles with hooks connected to a rope that is attached to a football goal post. The cost of this instrument set amounts to 13,390 baht, and the overall performance is rated as good. Students who used these learning instruments for improving movement and balance demonstrated a satisfactory level of physical fitness and were able to exercise correctly according to their physiological conditions, resulting in improved physical health. Furthermore, this research contributes to the knowledge of teachers at Thammikkawittaya School in Phetchaburi Province regarding appropriate exercise activities for students with visual impairment.